The study of ceramic pigments of spinel type with the use of slag of aluminothermal production of ferrotitanium - Zaychuk, Alexander; Iovleva, Julia (Publishing House of Lviv Polytechnic National University, 2013)
The article deals with the results of theoretical and experimental research on the production of ceramic pigments of blue color with the structure of spinel on the basis of slag of aluminothermal production of ferrotitanium. The sequence of the physical and chemical processes that determine the formation of the set of crystalline phases under drossy pigments burning was established. The influence of the concentration of cobalt oxide and the temperature of researched pigments firing on their optical-color characteristics was studied. The application of the developed pigments for glaze coatings painting was shown. У статті розглянуті результати теоретичних і експериментальних досліджень з отримання керамічних пігментів синьої колірної гами зі структурою шпінелі на основі шлаку алюмінотермічного виробництва феротитану. Встановлена послідовність протікання фізико-хімічних процесів, які обумовлюють формування заданих кристалічних фаз при випалі шлакoвмісних пігментів. Вивчений вплив концентрації оксиду кобальту і температури випалу дослідних пігментів на їх оптико-колірні показники. Показана перспективність використання розроблених пігментів для забарвлення глазурних покриттів.
Вивчення керамічних пігментів шпінельного типу з використанням шлаку алюмінотермічного виробництва феротитану
Keywords: color; IR-spectroscopy; ceramic pigments; phase composition; optical-color indicators; X-ray phase analysis; slag; забарвлення; ІЧ-спектроскопія; керамічні пігменти; кристалофазовий склад; оптико-колірні показники; рентгенофазовий аналіз; термодинамічні розрахунки; шлак